Electrocatalytic Oxidation of Ethanol on Flexible Three‐dimensional Interconnected Nickel/Gold Composite Foams in Alkaline Media. Issue 3 (10th December 2018) - Hatamie, Amir; Rezvani, Ehsan; Rasouli, Armin Sedighian; Simchi, Abdolreza
Abstract: In this work, a porous and flexible three‐dimensional (3D) nickel/gold nanoparticle electrode (NiF/AuNPs) is presented as an efficient electrocatalyst for ethanol oxidation in alkaline media. The 3D nanocomposite electrode consists of interconnected porous nickel foam (NiF) with large pores (500±200 μm diameter) surrounded by interconnected struts (∼100 μm) that are decorated with gold nanoparticles (AuNPs, 37±8 nm) through in‐situ electrochemical deposition. The catalytic performance of the 3D electrode was evaluated by different electrochemical methods. An enhancement in the performance (about 253 %) and a remarkable decline in onset potential (about ∼0.63 V) in comparison with pristine NiF for ethanol oxidation are demonstrated. This potential is lower than many reported results except palladium‐ and platinum‐based catalysts, which are expensive. It is shown that both hydroxyl anions and cations affect the ethanol oxidation on the 3D electrode. The interconnected porous structure provides efficient mass diffusivity, which along with its high specific surface area combined with the catalytic nature of AuNPs, may open new opportunities for in‐inexpensive and highly efficient electro‐oxidation of ethanol for energy applications. Abstract :